PARTISIPASI MASYARAKAT DALAM MENINGKATKAN KUALITAS KEBIJAKAN PENDIDIKAN DI PESANTREN MODERN - Kholik, Muhammad Habib Ilham; Fadriati, Fadriati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The quality of education is one of the indicators in determining the success in education, in improving the quality of education it is closely related to the surrounding environment which includes community participation. it is very important to understand what form of participation is appropriate for the community to support the creation of an increase in the quality of education, by using descriptive qualitative methods and with fact and data analysis techniques it is hoped that it will be able to analyze more in what form of participation is needed in improving the quality of education. The results obtained from this study are that community participation is needed both directly and indirectly, cooperation from the school is also important to socialize what forms of participation the community can provide to support the educational process, so collaboration, communication and relationships are needed. between the community and schools in creating participation in improving the quality of education.